2002
DOI: 10.1128/aem.68.9.4689-4693.2002
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Assimilation by Lactic Acid Bacteria and Bifidobacteria Isolated from the Human Gut

Abstract: The objective of this study was to evaluate the effect of human gut-derived lactic acid bacteria and bifidobacteria on cholesterol levels in vitro. Continuous cultures inoculated with fecal material from healthy human volunteers with media supplemented with cholesterol and bile acids were used to enrich for potential cholesterol assimilators among the indigenous bacterial populations. Seven potential probiotics were found: Lactobacillus fermentum strains F53 and KC5b, Bifidobacterium infantis ATCC 15697, Strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
270
2
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 397 publications
(296 citation statements)
references
References 22 publications
16
270
2
8
Order By: Relevance
“…Results from several in vitro studies indicate that some strains of lactobacilli and bifidobacteria are able to reduce the concentration of cholesterol in a culture medium when grown under anaerobic conditions in the presence of bile acid (Tahri et al, 1996;Brashears et al, 1998;Pereira and Gibson, 2002). Likewise strains of B. animalis isolated from feces have shown to possess bile salt hydrolase activity (Tanaka et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Results from several in vitro studies indicate that some strains of lactobacilli and bifidobacteria are able to reduce the concentration of cholesterol in a culture medium when grown under anaerobic conditions in the presence of bile acid (Tahri et al, 1996;Brashears et al, 1998;Pereira and Gibson, 2002). Likewise strains of B. animalis isolated from feces have shown to possess bile salt hydrolase activity (Tanaka et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that some lactic acid bacteria may secrete high-activity bile salt hydrolase (BSH) during metabolism, and this secretion could considerably affect cholesterol levels (Pereira & Gibson, 2002;Nguyen et al, 2007). Furthermore, BSH degrades cholates into amino acids and low-solubility free cholate in the enterohepatic circulation.…”
Section: Discussionmentioning
confidence: 99%
“…in n-3 PUFA-depleted mice (58). Moreover, it has been shown that an increase in lactic acid bacteria, such as Bifidobacterium spp., is related to a reduction in cholesterol absorption (154) and an increase in bile acid deconjugation, which leads to more excretion of bile acids and elimination of hepatic cholesterol (155).…”
Section: Introductionmentioning
confidence: 99%